Differential response of chlorophyll-a concentrations to explosive volcanism in the western South Pacific - Yoon, Joo-Eun; King, David; Longman, Jack; Cronin, Shane J. (Frontiers in Marine Science, 2023)
When it is deposited in the ocean, volcanic ash has the potential to release iron and other nutrients into surface water to stimulate ocean productivity. In the western South Pacific Ocean (SPO), one of the most important volcanic ash deposition regions, occasional widespread transport of volcanic ash may supply the nutrients not only locally around source islands but also within the wider the western SPO, accompanied by phytoplankton response. Through a comparative analysis of satellite and reanalysis data for the past 19 years (2004–2022), this study reveals that four explosive volcanic eruptions, Rabaul volcano, Papua New Guinea (October, 2006), Ambae volcano, Vanuatu (July, 2018), Ulawun volcano, Papua New Guinea (June, 2019), and Hunga volcano, Tonga (January, 2022), had the most strong stratospheric injection (>15 km) and mass loading of volcanic materials over the wider the western SPO (covering an area of >765,000 km2). The transport of 2006, 2018, 2019 volcanic emissions, was not likely associated with significant ash deposition over the western SPO. However, the Hunga eruption led to the deposition of ash-laden volcanic plumes over a wide area (~2,000 km from source), and was followed by the increase in chlorophyll-a concentrations (Chl-a) in the region (~70% increase). Minor changes related to other nutrient sources (e.g., hydrothermal input) suggest a link between the increase in Chl-a and 2022 Hunga ash falls over the western SPO. Our results indicate that volcanic ash deposition has implications for phytoplankton productivity in the western SPO, and highlights the need for further research into understanding how nutrient supply alleviated limitations of phytoplankton at the community level.